The Archetypical Metaphor of Life as Dream and Its Literary Interpretations - Čiočytė, Dalia (Literatūra, 2008)
In the context of Western culture, the archetypical metaphor of life as a dream (or living in a dream) is firstly seen in the Bible as in “the grammar of literary archetypes” (Northrop Frye). It means the fragility of human life, the spiritual drowse or, on the contrary, the spiritual revelation (in the case of the prophetical dream). This article seeks to compare the functions of the metaphor in the works A Midsummer Night’s Dream (1595) by William Shakespeare, La vida es sueno (1635 ) by Pedro Calderon de la Barca and A Dream Play (1901) by August Strindberg, as well as in Lithuanian works by Zbignievas Morštynas, Vydūnas, Šatrijos Ragana. The conclusion is being made that the works by William Shakespeare, Pedro Calderon de la Barca and August Strindberg have in common their interest in the theological problematics of the free will. The works interpret the Christian doctrine of the free will in different ways and from different aspects. The works of Lithuanian literature also participate in the intertextual polylogue inspired by the metaphor of life as a dream. However, they have got another stresses, they foreground the meanings of the world’s fragility and human spirituality (as the negative of living in a dream).